Dielectric studies of phase transitions in (Pb1-xBax)ZrO3 - Pokharel B.P.; Pandey D. (My University, 2025)
Phase transitions in semiwet derived (Pb1-xBax)ZrO3 ceramics for the composition range 0≤x ≤0.30 have been investigated by dielectric measurements at various frequencies during heating and cooling cycles. The paraelectric (PE) to ferroelectric (FE) to antiferroelectric (AFE) sequence of phase transitions is observed for 0≤x<0.20. On increasing the Ba2+ content from x=0 to x =0.05, the thermal hysteresis associated with the AFE-FE phase transition increases from 11 to 100°C. This is attributed to the increase in the piezoelectric coupling between the strain and polarization. For x=0.20, the FE phase does not transform into the AFE phase on cooling. Pronounced deviations from the regular FE behavior are observed on increasing the Ba2+ content to x=0.25. For x=0.30, the temperatures corresponding to the peak values of the real and imaginary parts of the dielectric constant become frequency dependent indicating relaxor FE behavior. It is shown that the polar clusters present in the PE phase undergo Vogel-Fulcher type relaxational freezing in the relaxor FE phase. The results of temperature dependent polarization measurements confirm the findings of the dielectric studies. It is proposed that Ba2+ substitution modifies the AFE and FE interactions of the PbZrO3 matrix in such a manner that their strengths become comparable for x=0.30 leading to the glassy or relaxor behavior. © 2000 American Institute of Physics.